Perkembangan Tari Pakkuru Sumange’ Pada Masyarakat Suku Bugis di Desa Sungsang II Kecamatan Banyuasin II Kabupaten Banyuasin - Anwar Anwar; Endang Rochmiatun; Nurfitri Hadi (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This writing is entitled The Development of the Pakkuru Sumange Dance in Sungsang II Village, Banyuasin II District, Banyuasin Regency. In this paper, we discuss the history and function of Pakkuru Sumange' Dance and the Development of Pakkuru Sumange' Dance. In this paper, we use the historical method of Data Collection Techniques (Observation, Interview and Documentation) Research Approach (Qualitative) Research Data Sources (Primary and Secondary) Data Analysis Techniques (Data Reduction, Data Presentation and Conlusion Drawing) Research Locations (Library Studies, Field Studies). The theory used in this study is the theory of Fusion proposed by A.L. Kroeber. Pakkuru Sumange dance is a dance that invites invited guests as guests of honor.